In vitro synthesis of pre-proteins of vacuolar compartmented proteinase inhibitors that accumulate in leaves of wounded tomato plants - Nelson, Christopher E. (1980)
Two proteinase inhibitor proteins that are compartmented in leaf vacuoles (lysosomes) were synthesized in vitro. mRNA was isolated from 17-day-old expanding tomato leaves by extraction with chaotropic buffers followed by chromatography on oligo(dT)-cellulose and was translated with a rabbit reticulocyte lysate system. Preparations of mRNA from leaves of both wounded plants and unwounded plants directed the incorporation of equivalent amounts of label into trichloroacetic acid-precipitable proteins. Only mRNA from leaves of wounded plants directed label into proteins that could be immunoprecipitated with rabbit IgG specific for either inhibitor I or inhibitor II. These results indicate that the wound-induced accumulation of proteinase inhibitors I and II in leaf vacuoles is a result of the presence of translatable mRNA species not present in leaves of unwounded plants. Gel electrophoresis of the immunoprecipitates in NaDodSO(4)/urea/polyacrylamide gels revealed that inhibitors I and II were translated in vitro as precursors about 2000 daltons larger than the inhibitors found in leaves. The presence of the additional polypeptide sequences in the newly synthesized inhibitors indicates that the inhibitors are processed either during or after synthesis, and the presequences may be signal peptides that are part of the process of inhibitor transport into the vacuolar compartments of tomato leaf cells.